2020
DOI: 10.1177/0022429420953118
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Influence of Performance in School Music Programs: A Grounded Theory

Abstract: The purpose of this grounded theory research was to investigate music teachers’ perceptions of the role and influence of performances in K–12 music programs and the processes by which these performances impact music teaching and learning. Three specific research questions informed this study: (1) What role do performances play in school music programs? (2) How are music teachers’ pedagogical decisions informed or influenced by their efforts to mount performances? and (3) What other aspects of the music teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Wadiyo, W et al argued that proper singing activities require some systematic learning, used data collection techniques and interactive communication methods to explore the basic skills of singing activities with students and teachers as the subjects of the study, and suggested that choosing the right vocal music and techniques for the singer is important [10]. Haning, M focused on the perceptions of music teachers about vocal performance in terms of the roles, teaching decisions, and student effort to explore the roles that influence vocal teaching and using five themes to describe the interaction between performance and vocal music [11]. Martin et al argued that musical scores convey a wide range of information, describing the significance of the construction of musical scores, and arguing that performers can know how to sing through the scores, demonstrating that music conforms to the same language as the communicative role of text [12].…”
Section: Introductionmentioning
confidence: 99%
“…Wadiyo, W et al argued that proper singing activities require some systematic learning, used data collection techniques and interactive communication methods to explore the basic skills of singing activities with students and teachers as the subjects of the study, and suggested that choosing the right vocal music and techniques for the singer is important [10]. Haning, M focused on the perceptions of music teachers about vocal performance in terms of the roles, teaching decisions, and student effort to explore the roles that influence vocal teaching and using five themes to describe the interaction between performance and vocal music [11]. Martin et al argued that musical scores convey a wide range of information, describing the significance of the construction of musical scores, and arguing that performers can know how to sing through the scores, demonstrating that music conforms to the same language as the communicative role of text [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, people's understanding of the importance and necessity of music education and its rich connotations is not yet consistent. In specific work, music education is often treated as dispensable content, focusing only on making superficial articles and superficially recognizing music education as merely singing and dancing [5][6][7]. The role of music education in assisting students in establishing the correct aesthetic ability and cultural cultivation, as well as comprehensively improving their talent quality, is not widely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Xianzhi Xia, Shuqiong Yang and Zhuyue Xie. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] …”
mentioning
confidence: 99%
“…Now teachers are being asked to share the work of selecting and preparing music for performance with student learners. This takes more class time and more planning, and is something that teachers can easily feel that they don’t have time for (Haning, 2021).…”
mentioning
confidence: 99%
“…However, an important benefit to a shift toward teaching all parts of the standards is that it makes assessment easier. In one study, teachers reported feeling uncomfortable about assessing final performances of students (Haning, 2021). Other teachers realize that assessing non-musical objectives of a concert (e.g., students being on time or wearing the appropriate uniform) is not a valid assessment of student learning (Shaw, 2021).…”
mentioning
confidence: 99%